Effective prevention of sports injuries: a model integrating efficacy, efficiency, compliance and risk-taking behaviour. Issue 8 (9th April 2008) - Van Tiggelen, D; Wickes, S; Stevens, V; Roosen, P; Witvrouw, E
Abstract : In 1992 van Mechelen et al published a "sequence of prevention model" based on a four-step process. This model has been widely used to implement preventive measures in response to sports injuries. However, the execution of this model has been shown to lack validity in determining the success of a preventive measure. A modified model has therefore been proposed which incorporates additional steps that enable the inclusion of external factors with a significant effect on the outcome of a prevention intervention. This expansion of van Mechelen's model leads to a more global model in which the compliance level and risk-taking behaviour of the individual and the assessment of efficiency of the stakeholders have a key influence on the preventive measure. This model gives a better insight into the different processes in injury prevention that can be used by clinicians, coaches and managers to decide whether to implement a preventive measure programme.